Hubungan EMS dan GSCM pada UMKM Batik sebagai Pilar Sustainable Green Management System - Siti Nurhayati; Wenti Ayu Sunarjo; Teresa Frietas Belo; Arum Ardianingsih (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2025)
The purpose of this research is to explore the relationship between environmental management system and green supply chain management as a complement to the sustainable green management system empirically and practically in the Kusuma batik community of Pekalongan City. The type of research is a quantitative research with a survey method using a questionnaire with saturated sampling techniques. The population is 32 batik MSMEs who are members of the Kusuma batik village association and have carried out environmentally friendly practices. The results of the study were obtained that there is a positive and significant influence between the environmental management system on sustainability, there is a positive and significant influence between green supply chain management on sustainability, and the exploration of the relationship between environmental management system and green supply chain management in batik MSMEs can be a complement to the sustainable green management system/green supply chain management both empirically and practically in the Kusuma batik community The city of Pekalongan will have an impact on sustainability in three aspects, namely economic, environmental and social. EMS is able to improve the performance of the organization's environment, so that it needs to be adopted, in addition to EMS also needs to facilitate the implementation of green supply chain management and institutional pressure because both are sustainable green management practices.